EKSISTENSI IBU SEBAGAI PENDIDIK ANAK USIA DINI DAN DAMPAKNYA BAGI KUALITAS PENDIDIKAN ANAK - Kasmiati Kasmiati (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Dampal Selatan, 2018)
Mothers are the first and most important educators in the family, in family education in the view of Islam parents who introduce early on Islamic values, introduce the norms prevailing in society, and teach how to interact among peers from an early age through, habituation, or role model, Developing Child Personality for example giving encouragement or motivation, then family will greatly affect to the quality of education of anak.oleh because of education of Islam give guidance for mother to educate children quality, such as giving enough attention to child, prepare or share time for work and family (children) so as not abandoned children's education. In punishment of children must be educational.